2020
DOI: 10.1590/1809-4392201804453
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of the nocturnal boundary layer in the central Amazon during the dry season

Abstract: In this study, the erosion of the nocturnal boundary layer (NBL) was analyzed in the central Amazon during the dry season of 2014, using data from the GoAmazon 2014/5 Project and high-resolution model outputs (PArallelized Les Model - PALM). The dataset consisted of in situ (radiosonde) and remote sensing instruments measurements (Ceilometer, Lidar, Wind Profiler, microwave radiometer, and SODAR). The results showed that the NBL erosion occurred, on average, two hours after sunrise (06:00 local time), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In contrast, the year 2015 registered a significant reduction (approximately 30 %) of the total rainfall in relation to the previous year, with a total accumulation of 1764 mm, well below the normal climatological average. This reduction is associated with the occurrence of the El Niño-Southern Oscillation (ENSO) event of that year (ECMWF, 2017;Macedo and Fisch, 2018;Newman et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the year 2015 registered a significant reduction (approximately 30 %) of the total rainfall in relation to the previous year, with a total accumulation of 1764 mm, well below the normal climatological average. This reduction is associated with the occurrence of the El Niño-Southern Oscillation (ENSO) event of that year (ECMWF, 2017;Macedo and Fisch, 2018;Newman et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…During IOP4, the total accumulated precipitation was well below the normal climatological value, as well as in comparison to the same period in 2014 (IOP2), with a total registered precipitation of 68 mm, a reduction of approximately 65 % compared to IOP2. This occurred due to the EN event being more intense during these months (ECMWF, 2017;Newman et al, 2018). The ENSO event (2015/2016) was considered one of the most intense in recent years, with an intensity similar to that which occurred during 1982/83 and 1997/98 (ECMWF, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With moisture freely available during the wet season, any conditional instability that favors cloud development such as surface heating or local instabilities can trigger 255 convection, thus lowering the PBL. Carneiro (2018) and Carneiro et al (2020), using observational data from ceilometer, LIDAR, and LES simulations shown that the erosion of the nocturnal boundary layer occurs 2 hours after the sunrise during the dry season and 3 hours after the sunrise during the wet season.…”
Section: Planetary Boundary Layer Analysis 240mentioning
confidence: 99%